What’s behind digital governance? Uncovering corruption loopholes in e-procurement in East Java - Eko Supeno; Nurul Jamila Hariani; Agie Nugroho Soegiono; Achsania Hendratmi; Filidyo Bramanta Adi Santoso; Muhammad Farrel (Integritas: Jurnal Antikorupsi, 2025)
Despite the growing presence of digital governance in Indonesia's public procurement system, corruption remains widespread. This study critically examines the limits of electronic procurement (e-procurement) as an anti-corruption instrument, with a focus on procurement processes in East Java Province. This study uses secondary data from the Corruption Eradication Commission's (KPK) Corruption Prevention Integrity Survey (SPI), as well as qualitative insights from focus group discussions (FGDs), in-depth interviews, and direct observations, to demonstrate that digitalization alone does not eliminate procurement corruption. The findings highlight pseudo transparency, in which procurement players exploit regulatory gaps notwithstanding electronic surveillance. Corruption is most frequent in areas with large procurement expenditures, inadequate supervision, and minimal public watchdog participation. The continued presence of favoritism, collusion, and selective vendor nominations, demonstrates that e-procurement may improve procedural transparency but fails to address underlying structural concerns. The study emphasizes the importance of independent supervision systems and leadership commitment to enhancing procurement integrity. By highlighting existing weaknesses in digital procurement systems, this study contributes to policy discussion about increasing governance integrity. It advocates for a resilient anti-corruption ecosystem that includes institutional reforms, increased enforcement, and civil society engagement, in addition to technology solutions.